Sounds of vacation : political economies of Caribbean tourism - Guilbault, Jocelyne; Rommen, Timothy (Duke University Press, 2019)
The contributors to Sounds of Vacation examine the commodification of music and sound at popular vacation destinations throughout the Caribbean in order to tease out the relationships between political economy, hospitality, and the legacies of slavery and colonialism. Drawing on case studies from Barbados, the Bahamas, Guadeloupe, Saint Martin, and Saint Lucia, the contributors point to the myriad ways live performances, programmed music, and the sonic environment heighten tourists' pleasurable vacation experience. They explore, among other topics, issues of authenticity in Bahamian music; efforts to give tourists in Barbados peace and quiet at a former site of colonial violence; and how resort soundscapes extend beyond music to encompass the speech accents of local residents. Through interviews with resort managers, musicians, and hospitality workers, the contributors also outline the social, political, and economic pressures and interests that affect musical labor and the social encounters of musical production. In so doing, they prompt a rethinking of how to account for music and sound's resonances in postcolonial spaces.Contributors. Jerome Camal, Steven Feld, Francio Guadeloupe, Jocelyne Guilbault, Jordi Halfman, Susan Harewood, Percy C. Hintzen, Timothy Rommen.